2011
DOI: 10.1007/s00330-011-2143-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in radiological patterns, tumour characteristics and diagnostic precision between digital mammography and screen-film mammography in four breast cancer screening programmes in Spain

Abstract: PPVs were higher when DM was used, both for further assessments and for invasive procedures, with similar cancer detection rates and no statistically significant differences in tumour characteristics. The greatest improvements in PPVs were found for masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
4
29
1
Order By: Relevance
“…A large number of studies have reported the superior detection of DCIS with digital than SFM. 60,[64][65][66][67][68] Among 200,000 females screened over a 6-year period, DCIS was accurately found in 0.09% of the females screened by digital means compared with 0.05% by SFM (p 5 0.010). 23 The most common radiographic appearance of DCIS is microcalcification.…”
Section: Screening Protocolmentioning
confidence: 95%
See 1 more Smart Citation
“…A large number of studies have reported the superior detection of DCIS with digital than SFM. 60,[64][65][66][67][68] Among 200,000 females screened over a 6-year period, DCIS was accurately found in 0.09% of the females screened by digital means compared with 0.05% by SFM (p 5 0.010). 23 The most common radiographic appearance of DCIS is microcalcification.…”
Section: Screening Protocolmentioning
confidence: 95%
“…23 The most common radiographic appearance of DCIS is microcalcification. 60,66,69 A study demonstrating CAD's ability to identify 100% of cases presenting with microcalcifications provides a plausible explanation for the superior detection of benign and in situ lesions in the digital setting. 70 A meta-analysis assessing the use of CAD against the interpretation of soft-copy digital mammograms alone showed that CAD significantly elevated the FP rate by an additional 1.19% over the rate observed with unassisted reporting (11%).…”
Section: Screening Protocolmentioning
confidence: 99%
“…Of the studies that 3examined the effect of DM in breast screening programs (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), five compared DM with SFM in concurrent cohorts (20,21,23,25,27), using mainly DR technology. Most found similar cancer detection rates (20,21,23) and positive predictive values (20,21,25) but also reported significantly higher recall rates for DM than for SFM (20,25).…”
Section: Study Populationmentioning
confidence: 99%
“…The proportion of DCIS was also higher in digital mammography group than SFM in a study by Domingo et al [12] , although this difference was not significant. This is in agreement with many previous studies [5,8] as well as our own study.…”
Section: Discussionmentioning
confidence: 79%
“…A number of studies have been conducted to compare screen-film with digital mammography and results have shown that digital imaging is as good as SFM in population based screening practices [4][5][6][7][8] , although most of these studies rely on surrogate end points such as cancer detection rate, recall rate and tumour characteristics at diagnosis. Few studies have been done within an operational national screening programme [9][10][11][12] . Accurate evaluation of risks and benefits of digital imaging in the screening environment is necessary at a time when the value of screening itself is questioned [13,14] .…”
Section: Introductionmentioning
confidence: 99%